2002
DOI: 10.1086/339342
|View full text |Cite
|
Sign up to set email alerts
|

A Recombinant Blood‐Stage Malaria Vaccine ReducesPlasmodium falciparumDensity and Exerts Selective Pressure on Parasite Populations in a Phase 1–2b Trial in Papua New Guinea

Abstract: The malaria vaccine Combination B comprises recombinant Plasmodium falciparum ring-infected erythrocyte surface antigen and 2 merozoite surface proteins (MSP1 and MSP2) formulated in oil-based adjuvant. A phase 1-2b double-blind, randomized, placebo-controlled trial in 120 children (5-9 years old) in Papua New Guinea demonstrated a 62% (95% confidence limits: 13%, 84%) reduction in parasite density in children not pretreated with sulfadoxine-pyrimethamine. Vaccinees had a lower prevalence of parasites carrying… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
368
1
4

Year Published

2002
2002
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 482 publications
(385 citation statements)
references
References 29 publications
8
368
1
4
Order By: Relevance
“…In particular, the increase in the proportion of FC27 family infections with age and the higher parasite densities associated with this family confirm the previous findings from both Papua New Guinea (Felger et al, 1994) and Tanzania , which suggested that the alleles of the FC27 family were more successful in evading the host's immune response. In support of this, both a case control study, and a vaccine field trial in Papua New Guinea found that FC27-type alleles were strongly associated with malaria morbidity (Engelbrecht et al, 1995;Genton et al, 2002). Another study at the same site found that asymptomatic 3D7 family infections appeared to protect against subsequent morbidity, but FC27 family infections did not (Al Yaman et al, 1997b).…”
Section: Discussionmentioning
confidence: 88%
“…In particular, the increase in the proportion of FC27 family infections with age and the higher parasite densities associated with this family confirm the previous findings from both Papua New Guinea (Felger et al, 1994) and Tanzania , which suggested that the alleles of the FC27 family were more successful in evading the host's immune response. In support of this, both a case control study, and a vaccine field trial in Papua New Guinea found that FC27-type alleles were strongly associated with malaria morbidity (Engelbrecht et al, 1995;Genton et al, 2002). Another study at the same site found that asymptomatic 3D7 family infections appeared to protect against subsequent morbidity, but FC27 family infections did not (Al Yaman et al, 1997b).…”
Section: Discussionmentioning
confidence: 88%
“…The fact that drug resistance becomes a problem within 5-30 years of first using a drug is indicative of their potential to evolve rapidly (Peters 1987). Changes in population frequencies of antigenic types after a field vaccine trial (Genton et al 2002) have already been documented, and escape mutants under vaccine pressure in experimental systems have also been observed (David et al 1985). Our theoretical model, which was based on well-known parameter values derived from field data (Dietz et al 1980;Aron & May 1982;Nedelman 1984;Struchiner et al 1989), predicts that a new virulent mutant will reach a frequency of 50% in less than 40 years (Gandon et al 2001 adaptation was purely phenotypic and these changes were carried over to new hosts, i.e.…”
Section: Implications For Vaccines and Other Control Measuresmentioning
confidence: 96%
“…However, the inhibition of merozoite invasion obtained with monoclonal antibodies has not been induced to date by immunisation. [36][37][38] Several other molecules are being channelled into human trials on the basis of results considered promising and obtained in one of the primate, mouse, or in-vitro models (figure 1). [39][40][41][42][43] Clinical trials will be essential to show whether these results can be extended to human beings.…”
Section: Personal Viewmentioning
confidence: 99%